1965
DOI: 10.6028/jres.069d.099
|View full text |Cite
|
Sign up to set email alerts
|

International comparison of atomic frequency standards via VLF radio signals

Abstract: A study was mad e of data obtained over an 18·month period (July 1961to December 1962 on th e co mpari so n of atomic frequency s tandard s located in se ve n laboratories in the Un ited States, Europe, and Ca nada, using th e VLF signals of eBR (16 kc/s), Rugby, England, and NBA (18kc/s), Balboa, Canal Zone. Eac h laboratory observes th e accu mulated diffe ren ce in phase over a 24-hr period (the sa me for a ll laboratories, or nea rly so) be twee n its own sta ndard (e ith e r laboratory or commerciaUy co n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1967
1967
1967
1967

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Since the Twelfth General Conference of Weights and Measures authorized a temporary atomic designation for the physical measurement of time in October 1964 (General Conference of Weights and Measures XII, 1964), these comparisons of atomic frequency standards have taken on added significance. This paper supplements a previous 18-month comparison of atomic frequency standards (Morgan, Crow, and Blair, 1965) and covers the period 1961 up through part of 1966. Many previous comparison studies through VLF and LF radio transmissions have been reported.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Since the Twelfth General Conference of Weights and Measures authorized a temporary atomic designation for the physical measurement of time in October 1964 (General Conference of Weights and Measures XII, 1964), these comparisons of atomic frequency standards have taken on added significance. This paper supplements a previous 18-month comparison of atomic frequency standards (Morgan, Crow, and Blair, 1965) and covers the period 1961 up through part of 1966. Many previous comparison studies through VLF and LF radio transmissions have been reported.…”
Section: Introductionmentioning
confidence: 93%
“…The methods of comparison and statistical analysis have been described by Morgan, Crow, and Blair (1965 • z BodUy (1966}: .Boctl.ly, Hartke, andHyatt (1966) . Initial analysis of these data yields the long-term mean of the daily observations at each receiving laboratory and the variance ST (or standard deviation Si) of these observations.…”
Section: Summary Of Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…There are about seven stations broadcasting standard frequency and time signals in the LF band, with transmitted frequency and time interval accuracies ranging from 0. propagation and the improvements in the accuracy of the atomic standards and the VLF receiving equipment, frequency comparisons over long distances with precisions better than one part in 10' ' are now possible. For example, an analysis of data on the comparison by VLF for an 18month period of several widely separated atomic frequency standards [25], [26] indicated that long-term precisions of this order are realizable. Although the analyses did not separate the fluctuations due to the propagation medium from those due to the transmitter or receiving system, the internal consistency of results indicated that the propagation effects were not limiting the measurements.…”
Section: B Distribution By Lf Transmissions (30 To 300 Khz)mentioning
confidence: 99%